EFFECT OF RECREATION ON DIVERSITY OF LITTORAL BENTHIC MACROINVERTEBRATES IN LAKES - Koszałka, Jacek (Polish Journal of Natural Sciences, 2024)
Water-based recreation making use of the assets offered by the lakes. The impact of recreational activities on the macroinvertebrate communities in the littoral zone was investigated by comparing sites that had been altered for recreational purposes with sites that had not been used for this purpose. The study was conducted on fourteen lowland lakes situated in the north-eastern region of Poland. A semi-quantitative method was used to sample the infralittoral macroinvertebrates at the recreationally used site and two reference sites. The results obtained indicate that the development of recreational facilities has a moderate impact on macroinvertebrate assemblages. Significant differences (Wilcoxon test, p < 0.05) were identified in the macroinvertebrate assemblages of the compared sites in eight of the fourteen studied lakes. The observed biodiversity was predominantly lower compared to the reference sites, and the differences in community structure may be the result of the homogeneity of the littoral habitats. In part of the lakes surveyed, macroinvertebrate communities were found to be similar between those used for recreation and sites that had been transformed for recreational functions.